Teste imunoenzimático com base em anticorpo monoclonal para a detecção de anticorpos contra herpesvírus bovino tipos 1 e 5. - Bauermann, Fernando Viçosa (2009)
This dissertation reports the standardization of a monoclonal antibody (MAb)-based immunoenzymatic test (ELISA) for detection of antibodies to bovine herpesvírus types 1 and/or 5 (BoHV-1 and BoHV-5). The initial steps involved the determination of the most suitable MAb, the appropriate dilutions of viral antigen and test sera; and the cut-off value of the assay. After standardization, the ELISA was validated by testing 506 cattle serum samples previously tested for neutralizing antibodies to BoHV-1 and BoHV-5 by virus neutralizing (VN) assay. Comparing to the VN for BoHV-1 antibodies, the ELISA presented sensitivity and specificity of 96.6% and 98.3%, respectively. Positive and negative predictive values were 97.6%, the concordance between the tests was 97.6% and the coefficient of correlation k (kappa) was 0.95, demonstrating an excellent correlation. Comparing to the VN for BoHV-5 antibodies, the ELISA presented 94.3% of sensitivity, 97.9% of specificity, 97.1% of positive predictive value, 95.9% negative predictive value, concordance of 96.4% and kappa coefficient of 0.92. These results demonstrate that the ELISA presents suitable specificity and sensitivity to be used for individual and herd serological diagnosis of BoHV-1 and BoHV-5, thus, representing an alternative for VN assays and imported ELISA kits.